Big push versus absorptive capacity: How to reconcile the two approaches - Patrick Guillaumont; Sylviane Guillaumont Jeanneney (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
We argue in this paper that cancelling the debt of the poorest countries was a good thing, but that it should not imply that the debt instrument should be foregone. Debt and debt cancellations are indeed two complementary instruments which, if properly managed, perform better than either loans or grants taken in isolation. The core of the intuition, which we develop in a simple two-period model, relates to the fact that the poorest countries are also the most volatile, so that contingent facilities, explicitly incorporating debt cancellation mechanisms, are a valuable instrument.
Keywords: F34; F35; 330; grants; loans; developing countries; Entwicklungshilfe